2022
DOI: 10.5935/1518-0557.20220009
|View full text |Cite
|
Sign up to set email alerts
|

Link between cesarean section scar defect and secondary infertility: Case reports and review

Abstract: The objective was to study clinical cases and understand the link between cesarean section scar defect with hydrometra and secondary infertility. A retrospective case series from an assisted reproductive center and infertility treatment clinic in the United Arab Emirates. We had five patients with secondary infertility diagnosed with cesarean section scar defect with persistent hydrometra based on high resolution transvaginal ultrasound assessment. The patients underwent surgical repair for the cesarean sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Data extraction was performed on the 100 articles that met inclusion criteria. These included four systematic reviews [3 [12][13][14][15][16][17][18]; two randomized control trials [19 ]; 12 video articles [62][63][64][65][66][67][68][69][70][71][72][73], 10 case reports [74][75][76][77][78][79][80][81][82][83]; one case series [84]; and 21 conference abstracts [64,. Excluding the conference abstracts, 25 countries were represented as the country of correspondence of the first author of the remaining 79 publications.…”
Section: Resultsmentioning
confidence: 99%
“…Data extraction was performed on the 100 articles that met inclusion criteria. These included four systematic reviews [3 [12][13][14][15][16][17][18]; two randomized control trials [19 ]; 12 video articles [62][63][64][65][66][67][68][69][70][71][72][73], 10 case reports [74][75][76][77][78][79][80][81][82][83]; one case series [84]; and 21 conference abstracts [64,. Excluding the conference abstracts, 25 countries were represented as the country of correspondence of the first author of the remaining 79 publications.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1955 women with PL, 20.46% had a previous live birth, of which 32.91% were delivered by cesarean section, which increased the risk of subsequent infertility in women with PL, but had no effect on the ongoing pregnancy and live birth in subsequent pregnancies. In recent years, the relationship between cesarean scar uterus and subsequent secondary infertility has been gradually recognized, but the specific mechanism is not clear [ 20 , 21 ]. Nobuta et al found that a cause of secondary infertility in women with cesarean scar syndrome may be chronic inflammation of the uterine cavity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature analysis shows that various mechanisms have been proposed to explain how the collection of endouterine fluid (hydrometra) associated with isthmocele may interfere with the embryo implantation process in uterine tissue [78,79]. Previous studies have demonstrated that surgical intervention to correct defects in the cesarean scar can effectively restore uterine anatomy to a normal condition, thus preventing the accumulation of fluid within the endometrial cavity [80].…”
Section: Infertilitymentioning
confidence: 99%